National survey revealed variable practices in paediatric procedural sedation and patient monitoring. Issue 6 (9th March 2021) - Tervonen, Miikka; Kallio, Merja; Peltoniemi, Outi
Abstract: Paediatric procedures requiring sedation are increasingly being performed off site, but there are no national guidelines for paediatric procedural sedation in Finland or studies on it. Therefore, the aim of this survey was to assess national practices for paediatric procedural sedation outside operation rooms and intensive care units in terms of indications, sedative medication, treatment facilities, patient safety and training of the personnel. An online survey including single‐ and multiple‐choice questions and open‐ended questions was sent to Finnish paediatricians, paediatric surgeons and paediatric anaesthesiologists via the electronic mailing lists of national societies in December 2019. A total of 71 responses were received. Lumbar puncture (41%), intra‐articular injections (38%) and MRI (17%) were the most common procedures that required routine sedation. Benzodiazepines were the most frequently used sedatives during both painful procedures (80%) and imaging (61%). Pulse oximetry monitoring was reported by 75% of the respondents, but other physiological parameters were rarely monitored (ECG 28%; blood pressure 39%; respiratory rate 34%). The level of sedation was not objectively assessed. Adrenaline (72%) and equipment for managing adverse respiratory outcomes (supplemental oxygen 98%; ventilation equipment 92%) were available in most facilities in which sedation was performed. Only one‐third of the respondents had undergone training for paediatric procedural sedation, and only 39% of the hospital units compiled statistical data on sedation‐related adverse events. The paediatric procedural sedation practices vary across hospitals. National guidelines for patient monitoring and training of personnel could improve treatment quality and patient safety.